Book review: Julien Chaisse (Ed.), Sixty Years of European Integration and Global Power Shifts: Perceptions, Interactions and Lessons. Issue 4 (November 2020) - Erlings, Esther
Julien Chaisse (Ed.), Sixty Years of European Integration and Global Power Shifts: Perceptions, Interactions and Lessons . Oxford: Hart Publishing, 2020, £91.80, 520 pp., ISBN: 9781509933747.